2020
DOI: 10.1088/1742-6596/1661/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

The generalized correlating function of capillary curves and the relationship of the filtration-capacitive parameters of reservoirs in Western Siberia with the size distribution of pore channels

Abstract: It was shown that the Leverett J-function and the Brooks-Corey correlating function approximate the capillary curves with insufficient accuracy and therefore do not allow us to obtain an analytical expression for the density distribution of pore channels by size. The polynomial approximation proposed makes it possible to sharply increase the reliability and accuracy of the capillary curves approximation. We obtained analytical expressions that allow to get a density distribution function of pore channels by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…These depths are clearly confirmed by the volumes of infiltrates [1] extracted from the formations during well "testing" by formation testers.…”
Section: Introductionmentioning
confidence: 59%
“…These depths are clearly confirmed by the volumes of infiltrates [1] extracted from the formations during well "testing" by formation testers.…”
Section: Introductionmentioning
confidence: 59%
“…Therefore, the fight against sand-related problems in wells should begin during their construction through correct selection of working fluids. The work [4] studied the stability of sand arches in various forms of sand and the saturation of sand with fluids during fluid filtration. Laboratory studies revealed that the stability of arches depends on the degree of sand abrasion and fluid saturation.…”
Section: Methodsmentioning
confidence: 99%
“…Geological factors include: current net thickness of the reservoir, current oil and water saturation, clay and sand content, coefficient of the layer-by-layer heterogeneitynumber of reservoir beds, bound water, distance to the water-oil contact (which affects the initial water cut), porosity, permeability and flow capacitty, the current density of recoverable reserves per well. In the presence of complicating structural tectonic elements such as shears, faults, fractures, it is necessary to know the stress of the main stress axes and the geomechanical parameters that will affect the productivity after hydraulic fracturing [4,5].…”
Section: Methodsmentioning
confidence: 99%